Comparison of diameter-based and image-based measures of surface area from gross placental pathology for use in epidemiologic studies. (September 2018) - Freedman, Alexa A.; Kipling, Lauren M.; Labgold, Katie; Marsit, Carmen J.; Hogue, Carol J.; Rajakumar, Augustine; Smith, Alicia K.; Pinar, Halit; Conway, Deborah L.; Bukowski, Radek; Varner, Michael W.; Goldenberg, Robert L.; et al.
Abstract: Placental surface area is often estimated using diameter measurements. However, as many placentas are not elliptical, we were interested in the validity of these estimates. We compared placental surface area from images for 491 singletons from the Stillbirth Collaborative Research Network (SCRN) Study (416 live births, 75 stillbirths) to estimates obtained using diameter measurements. Placental images and diameters were obtained from pathologic assessments conducted for the SCRN Study and images were analyzed using ImageJ software. On average, diameter-based measures underestimated surface area by −5.58% (95% confidence interval: −30.23, 19.07); results were consistent for normal and abnormal shapes. The association between surface area and birthweight was similar for both measures. Thus, diameter-based surface area can be used to estimate placental surface area. Highlights: We compared placental surface area from images to area estimated using diameters. Manual outlines of placental area from images have excellent inter-rater reliability. Placental diameters are an adequate proxy for estimating surface area.